A new companion to digital humanities - Schreibman, Susan; Siemens, Raymond George 1966-; Unsworth, John 1958- (John Wiley & Sons Inc., 2016)
"A New Companion to Digital Humanities offers the most comprehensive and up-to-date collection of research currently available in this dynamic and burgeoning field"--Provided by publisher.